2019
DOI: 10.1039/c9sc00135b
|View full text |Cite
|
Sign up to set email alerts
|

A new post-synthetic polymerization strategy makes metal–organic frameworks more stable

Abstract: This work develops a new post-synthetic polymerization strategy to make various metal–organic frameworks more stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 64 publications
(66 reference statements)
2
82
0
Order By: Relevance
“…Since this work, a number of similar approaches have been developed and applied to improve MOF stability. [141][142][143][144] Qian et al successfully deposited a hydrophobic organosilicone layer on the exterior surface of MOFs via a facile solution-immersion process without any heat treatment. 141 Upon exposure to water for 5 days, it was found that the porosity of the MOFs HKUST-1, MIL-125, and ZIF-67 was retained to a great extent due to the enhanced hydrophobicity.…”
Section: Improving the Chemical Stability Of Existing Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this work, a number of similar approaches have been developed and applied to improve MOF stability. [141][142][143][144] Qian et al successfully deposited a hydrophobic organosilicone layer on the exterior surface of MOFs via a facile solution-immersion process without any heat treatment. 141 Upon exposure to water for 5 days, it was found that the porosity of the MOFs HKUST-1, MIL-125, and ZIF-67 was retained to a great extent due to the enhanced hydrophobicity.…”
Section: Improving the Chemical Stability Of Existing Mofsmentioning
confidence: 99%
“…Recently, Queen's group successfully developed a two-step postsynthetic polymerization method to improve the stability of seven different types of MOFs. 143 First, polydopamine (PDA) as an adhesive was rstly coated on the surface of these MOFs under an oxygen atmosphere. Then, based on a Michael addition, the hydrophobic 1H,1H,2H,2H-peruorodecanethiol was covalently graed on the surface of the MOF@PDA that resulted from the previous step.…”
Section: Improving the Chemical Stability Of Existing Mofsmentioning
confidence: 99%
“…The general concept is mainly directed towards rendering the MOF surface hydrophobic, in an attempt to enhance the resistance to moisture/water. This can be achieved through coating of the MOF, postsynthetically, with hydrophobic polymers . Alternatively, the incorporation of hydrophobic graphite oxide during MOF synthesis has been shown to enhance the hydrothermal stability and catalytic activity of HKUST‐1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it was demonstrated that in vivo chemo-photothermal treatment by sgc-8 aptamer-PDA-DOX/ZIF-8 and near infra-red illumination resulted in tumor elimination, without noticeable systemic toxicity and favorable biocompatibility. Yang et al applied a similar method for the surface functionalization of MOF, aiming to increase the hydrophobicity and water stability [101]. This time, it was based on the easy polymerization of free-base dopamine at room temperature under a mild oxygen atmosphere, affording a polydopamine layer on the MOF.…”
Section: Encapsulation Of Mof Into Polymersmentioning
confidence: 99%